Financial Management of Regional Public Service Agencies: an Analysis of Flexibility, Accountability, and Performance in the Perspective of Public Governance - Maulana, Ajie Cakra (International Journal Labs, 2026)
The Regional Public Service Agency (BLUD) is a strategic policy instrument in the reform of regional financial management in Indonesia, designed to address the limitations of a rigid public bureaucratic system that is often less responsive to public service needs. Providing financial management flexibility to BLUD is expected to improve efficiency, service quality, and regional fiscal sustainability. However, this flexibility also presents governance challenges, particularly regarding accountability, control, and alignment with public service goals. This article aims to analyze BLUD financial management through the synthesis of the New Public Management theoretical framework, public accountability theory, the principal–agent perspective, and the principles of good governance, relating these to the context of BLUD implementation in Indonesia. The methods used are qualitative, based on literature review, regulatory analysis, and national empirical practice studies. The results show that the success of BLUD financial management is largely determined by institutional capacity, the quality of human resources, integration of financial information systems, and the effectiveness of internal and external supervision mechanisms. This article contributes to the enrichment of regional public financial management literature and provides policy implications for local governments in designing BLUD strengthening strategies that are more accountable, efficient, and performance-oriented in delivering public services.